Pengabdian Masyarakat Melalui Pemeliharaan Peralatan Kesehatan Posyandu Lansia Amarta - Septi Aprilia; Ipin Prasojo; Eko Nugroho; Wahyu Priyono; Elsa Sari Hayunah Nurdiniyah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Posyandu is one of the UKBM managed by and from the community. In its implementation, medical devices play an essential role in Posyandu activities. Even though medical devices are rarely used, they must be cared for, cared for, and maintained. This is because medical devices are very influential in treating patients. Therefore, it is necessary to carry out a community service program through the maintenance of medical devices at the Posyandu. This community service aims to improve health services at the Amarta elderly Posyandu. The maintenance method includes observing, repairing, and re-applying the tool. Then proceed with counselling on the maintenance of medical devices. The result shows the medical devices could be appropriately reused, and there were no errors during the health service activities at the posyandu. It can be concluded that the repair, maintenance and counselling activities in the Amarta Elderly Posyandu equipment went smoothly.